True Grit - Henry Hathaway; Hopper, Dennis; Glen Campbell; Jeremy Slate; Kim Darby; Robert Duvall; John Wayne (USA Paramount Pictures, 1969)
The sudden death of her father sends a young tomboy of a girl, 'Mattie Ross' (Kim Darby) on a mission to find justice, and the avenging of her father's death. She recruits a tough old marshal in the person of Rooster Cogburn (John Wayne), because he has "grit", and a reputation of getting the job done. Mattie accompanies Cogburn, and also a Texas Ranger ('La Boeuf' played by Glen Campell; who is looking for 'Tom Chaney' [Jeff Corey] for a separate murder in Texas) as the leave from Fort Smith, Arkansas into the Indian Territory (present day Oklahoma) to find her father's killer.
A drunken, hard-nosed U.S. Marshal and a Texas Ranger help a stubborn young woman track down her father's murderer in Indian territory.
Charles Portis
Language(s): English
Subtitle(s): English, Turkish, Bulgarian
Keywords: Drama; Western; Adventure